2008
DOI: 10.1111/j.1747-0285.2008.00667.x
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Screening of Cathepsin K Inhibitors Using Docking and Pharmacophore Models

Abstract: Cathepsin K is a lysosomal cysteine protease that is highly and selectively expressed in osteoclasts, the cells which degrade bone during the continuous cycle of bone degradation and formation. Inhibition of cathepsin K represents a potential therapeutic approach for diseases characterized by excessive bone resorption such as osteoporosis. In order to elucidate the essential structural features for cathepsin K, a three-dimensional pharmacophore hypotheses were built on the basis of a set of known cathepsin K i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…The analysis of our PASS results clearly indicated that Rg3 showed significant predicted biological activity including the muscle weakness treatment, metabolic disorder treatment, transcription factor inhibitor, and transcription factor stimulant (Table ). Our results are in agreement with the previous results suggesting that different natural compounds have the inhibitory effect on the expression of Cat‐K (Ravikumar et al, ). Thus, these in silico results ascertained our hypothesis that Rg3 interacted with the targeted Cat‐K protein.…”
Section: Discussionsupporting
confidence: 94%
“…The analysis of our PASS results clearly indicated that Rg3 showed significant predicted biological activity including the muscle weakness treatment, metabolic disorder treatment, transcription factor inhibitor, and transcription factor stimulant (Table ). Our results are in agreement with the previous results suggesting that different natural compounds have the inhibitory effect on the expression of Cat‐K (Ravikumar et al, ). Thus, these in silico results ascertained our hypothesis that Rg3 interacted with the targeted Cat‐K protein.…”
Section: Discussionsupporting
confidence: 94%
“…Pharm-B exhibited a higher enrichment factor value (29.88) than Pharm-A (26.93). Generally, the goodness of fit (GH) scores ranged from 0, which indicates a null model, to 1, which indicates an ideal model 31 . Therefore, a model with a GH score that is greater than 0.6 and closer to 1 is expected to be more reliable in the screening of large chemical databases 32 .…”
Section: Resultsmentioning
confidence: 99%
“…Catalyst, a leading software for chemical featurebased pharmacophore modeling, is arguably the most widely used program. A number of previous studies focused on the validation of pharmacophore-based virtual screening -by evaluating pharmacophore models, by pharmacophore identification and by the associated methodologies for screening -with respect to the reproduction of the binding affinity or enrichment of hit lists from a database of decoys [24][25][26][27][28][29][30][31][32]. In this section, we focus on examples that have shown, to some extent, the successful application of pharmacophore-based virtual screening for new drug discovery.…”
Section: Recent Applications Of Pharmacophore-based Virtual Screeningmentioning
confidence: 99%